UiTM vehicle sticker serial number recognition using OCR with template matching / Nurul Syamimi Mohammod and Siti 'Aisyah Sa'dan - Mohammod, Nurul Syamimi; Sa'dan, Siti 'Aisyah (2015)
The level of safety around us has become critical nowadays. There is a need to enhance our security level in order to minimize the risk. In UiTM Terengganu, Polis Bantuan provide vehicle stickers for those who are qualified to bring vehicle to UiTM. These vehicle stickers is being used as an entrance and exit pass. The purpose of this vehicle stickers is to identify the vehicles which are allowed to pass in UiTM. UiTM vehicle sticker serial number (VSSNR) is a system where the serial number is recognized and identified and match to the corresponding plate number to ensure the validity of the sticker and the sticker is genuine. This project focuses on processing the image of UiTM vehicle sticker serial number and is developed to assist Polis Bantuan UiTM in verification of UiTM vehicle sticker. It applies the image processing techniques that manipulate image to text using optical character recogintion (OCR) with template matching. OCR is the process whereby typed or printed pages can be scanned into computer systems, and their contents recognized and converted into machine-readable code. To convert this, several steps are involved which included the process of grayscale, binarizing and slicing the image. This project may ease the Polis Bantuan in performing their task efficiently. In the future work, this project should be implement in mobile application because mobile area is prominent area nowadays.